Influence of Thermal Processing on the Physicochemical Properties, Stability and Antioxidant Activities of Rice Milk containing a Co-Encapsulated Powder of Black Rice and Green Tea - Salee, Nuttinee; Keshavan , Niranjan; Cheng, Qiaofen; Khalil Ghawi, Sameer; Naruenartwongsakuld, Srisuwan; Chaiyana, Wantida; Inpramoon, Aekarin; Utama-ang, Niramon (Food and Applied Bioscience Journal, 2024)
This study investigated the influence of various thermal processing methods on the physicochemical properties, total phenolic compounds (TPC), and antioxidant activities of Jasmin rice milk (JRM) enriched with a co-encapsulated powder of black rice and green tea (CEP). Higher concentrations of CEP in JRM enhanced TPC and antioxidant activities, particularly against DPPH and ABTS free radicals. However, preliminary acceptances including color, aroma, and overall appearance diminished at higher CEP levels. Optimal results were observed with a 2% CEP concentration. Thermal treatments at 121 °C for 35 min and 142 °C for 6 sec significantly altered viscosity, pH, and sedimentation stability. The principal component analysis revealed that samples treated at 63°C for 30 min and 72°C for 15 sec exhibited higher characteristics of lightness and viscosity, particularly in terms of TPC values and antioxidant activities. This research provides valuable insights into optimizing the heat treatment process for the application of JRM with CEP, highlighting the balance between processing effects and product quality.